(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Effective teaching begins with thoughtful planning. One of the key responsibilities of a teacher is to ensure that students receive well-structured and meaningful instruction. This process involves understanding the syllabus, planning lessons accordingly, and creating detailed lesson plans. In this article, we will explore the importance of syllabi, how educators can work with them effectively, and what goes into a strong lesson plan.